JABON (Anthocephalus cadamba Roxb.) POTENCY FOR REMEDIATING LEAD (Pb) TOXICITY UNDER NUTRIENT CULTURE CONDITION - Luluk Setyaningsih; Yadi Setiadi; Sri Wilarso Budi; Hamim Hamim; Didy Sopandie (BIOTROPIA, 2018)
Information on metal adaptation in plants is essential to understand the mechanism of heavy metal remediation, including lead (Pb), mediated by forest plants in contaminated land. This study aimed to identify the adaptation mechanism of jabon (Anthocephalus cadamba Roxb.) seedlings to excessive lead levels based on the tolerance index of growth performance and lead transport to plant tissue. The seedlings were exposed to lead Pb(NO₃)₂​ at concentrations of 0, 0.5, 1, 1.5, 5, and 10 mM in nutrient culture for 15 days. The results showed that the tolerance index (TI) of the seedlings significantly decreased with Pb exposure up to 1.5 mM, although the TI values remained above 75%. All seedlings died at Pb concentrations of 5 mM and above. Lead accumulated in all parts of the seedlings, with the highest concentration found in the leaves (735.9 ppm) under 0.5 mM Pb exposure. Pb was transported to the upper portion of the seedlings, as indicated by a transport factor (TF) greater than 1. The results suggest that jabon can tolerate excessive Pb exposure up to 1.5 mM and has potential as a phytoremediator plant.